Strategy for the Development of Waste Management at Padang State University - Widian Ningrum; Indang Dewata; Nurhasan Syah; Aulia Azhar; Dewi Rahmadani Siregar (Postgraduate, University of Mataram, 2026)
As centers of academic activity, universities generate significant waste volumes requiring systematic and sustainable management. This research aims to analyze the current state of waste management at Universitas Negeri Padang (UNP) across technical-operational, socio-institutional, economic, and regulatory dimensions; assess the participation level of the academic community; and formulate an efficient, sustainable development strategy. This study employed a qualitative descriptive method with a case study approach. Data were gathered through observation, interviews, questionnaires, and documentation studies. The strategic framework was developed using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, supported by Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The findings reveal that UNP’s current waste management remains conventional (collect-transport-dispose), handling 1.5 to 2 tons daily without integrated source-sorting. SWOT analysis identified strong internal legal foundations and a large human resource pool as primary strengths, while the conventional system and low community participation constitute main weaknesses. Although external threats include public apathy and landfill dependency, significant opportunities exist through governmental regulatory support and potential collaborations. With an IFAS score of 1.1 and an EFAS score of 0.29, UNP is positioned in the aggressive strategy (SO) quadrant. Furthermore, economic valuation indicates a potential daily revenue of IDR 1,545,100 from recyclable waste, highlighting the viability of an integrated system. To achieve sustainable management, UNP must leverage its internal strengths to seize external opportunities. The study recommends a transition from conventional methods to an integrated model by strengthening internal regulations, optimizing 3R (Reduce, Reuse, Recycle) infrastructure, implementing sustainable education programs, and fostering multi-stakeholder partnerships.